The party and political landscape of Germany after the European Parliament elections - Vladislav B. Belov (Научно-аналитический вестник Института Европы РАН)
On June 9, 2024, elections to the European Parliament were held in Germany. With active face-to-face and absentee voting, almost almost 65% of German voters cast their vote for one of the 35 German parties admitted to the electoral process. It is expected that the most votes were received by the affiliated parties. The main opposition forces – the CDU/CSU union and the protest Alternative for Germany – turned out to be the winners. The members of the government coalition were defeated, they gained almost the same number of votes in total as the Christian Democrats and their Bavarian partners. For the first time, citizens over the age of 16 took part in the elections. The author analyzes the election programs of the main parties and the voting results. In his opinion, they reflected the main processes taking place in the German party-political landscape over the past few years, including the ongoing fragmentation and change of electoral preferences. It is concluded that one of the main reasons for the changes is the rejection by German citizens of the policy of the «traffic light» government. The majority believes that it has proved unable to provide effective responses to numerous crises in the national economy. The article provides a forecast of the ability of government parties to continue their compromise-based activities and the possibility of maintaining the coalition until the next Bundestag elections in September 2025. The interim litmus test will be the upcoming September elections to the landtags of the three East German lands, in which the victory of the AFD is predicted.